Influência de diferentes protocolos de usinagem em CAD/CAM na adaptação e na anatomia de coroa de zircônia translúcida - Bringhenti, Indiarai Levandoski (2024)
Objective: to evaluate the adaptation, marginal integrity and occlusal anatomy of monolithic 3Y-TZP zirconia crowns machined using different CAD/CAM protocols. Methods: second premolar model was scanned and the crown was designed, 39 crowns were machined using different protocols (n=13): smooth, normal and fast. To evaluate the internal and marginal adaptation, the replica technique was used, which was sectioned in the mesio-distal direction and the crack thickness was measured in the regions. To assess marginal integrity, images of the crown margins were taken. For this assessment, a severity scale was followed with scores from 1 to 5. Data from both analyzes were analyzed with Kruskal Wallis and Student-Newman-Keuls (¿ = 0.05). For occlusal anatomy, a qualitative analysis of the images obtained was carried out in the stereomicroscope. Results: For adaptation, no difference was found between the groups in the marginal, gingival-axial and axial angle regions. In the axio-occlusal and occlusal angle, the smooth group showed greater crack thickness than the normal group. In marginal integrity there was no difference between the groups for total margin. Analyzing each region separately, the fast group had higher scores than the normal and smooth group in the mesial and vestibular regions. For qualitative analysis of occlusal anatomy, the soft group presented crowns with more refined occlusal anatomy. Conclusion: The type of machining affected the adaptation of the crowns in regions close to the occlusal surface. The protocols resulted in crowns with good marginal refinement, but with a different quality than the occlusal anatomy.